Validity, Practicality, and Effectiveness of Business Introduction Book Based on Theory and Practice - Sabda Dian Nurani Siahaan; Aurora Elise Putriku; Lenti Susanna Saragih (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this research is to obtain the teaching materials based on theory and practice for the Business Introduction course. This study use the ADDIE model for research and development, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (4) Evaluation. Validity, practicability and effectiveness, are the data analysis approaches used in this reserach. This book was validated by three validators, and the results reveal that it has good feasibility but should be revised. The results of the practical test also show that the book has a high level of practicality. According to the test findings, students' post-test scores are greater than their pre-test scores.